(untitled) (Research, Society and Development, 2020)
Objetive: The present study was to evaluate the acaricidal and larvicidal activity of the essential oil from Psidium rufum leaves against engorged Rhipicephalus microplus females and larvae. Methodology: Essential oil from fresh P. rufum leaves was extracted by hydrodistillation (2h) and analyzed by gas chromatography coupled to mass spectrometry (GC-MS). The acaricidal and larvicidal activities were performed using the adult immersion and larval immersion (Larval Paket Test) techniques using the essential oil at concentrations ranging from 300 to 0.001 mg/mL . As positive control was utilized as a commercial solution (15% cypermethrin; 25% chlorpyrifos; 1% citronellal) at 0.005%, and as negative control, an aqueous solution of 2.0% polysorbate (80) was used. Lethal concentrations (LC50 and LC99) were determined by Probit analysis. Results: In the essential oil, 55 compounds were identified, with hydrocarbon sesquiterpenes being the majority class (70.07%), with majority being 1.8-cineole (19.00%); followed by α-longipinene (18.62%). The results showed that the essential oil of P. rufum at 6.20 mg / mL was effective in controlling 73% of the hatchability of eggs, reducing oviposition and the number of adult ticks and larvae. The CL99 for larvae was 2.50 mg / mL, and for engorged females CL99 was 513.57 mg / mL. Conclusion: essential oil from P. rufum leaves demonstrated potential to control R. microplus in the life cycle that corresponds to the larval stage, indicating that it is a promising plant for the development and application of products against bovine ticks.